Attitudes and Behaviours of Health Workers and the Use of HIV/AIDS Health Care Services - Dapaah, Jonathan M. (Nursing Research and Practice, 2016)
Background. This article discusses how health workers relate to and communicate with clients of VCT and ART treatment. It also looks at how health worker practices in the form of attitudes and behaviours towards clients influence the use of these services. Methods. In-depth interviews, informal conversations, and participant observation were used to collect data from health workers providing VCT and ART and clients who access these services in two Ghanaian hospitals. Results. The study found that health workers providing these services, with the exception of a few, generally showed positive attitudes and behaviours towards clients during clinical encounters. Health workers warmly received clients to the facilities, addressing clients with courtesy, advising clients on a wide range of issues, sometimes supporting clients financially, and comfortably interacting with them. This is contrary to the findings of most studies in the literature that health workers often do not communicate and relate to these patients well. Conclusion. It concludes that dealing with clients well during interactions in the centres and clinics is crucial for reducing the perceived stigma associated with the use of services and increasing use as part of the national effort to reduce the infection rate of the disease in Ghana.